Monoclinic VO2(D) hollow nanospheres with super-long cycle life for aqueous zinc ion batteries. Issue 27 (2nd July 2019) - Chen, Linlin; Yang, Zhanhong; Huang, Yaoguo
Abstract : Monoclinic VO2 (D) hollow nanospheres are demonstrated to have long cyclic endurance stability in 3 M ZnSO4 electrolyte for aqueous zinc ion batteries. Abstract : Vanadium dioxide (VO2 ) is a very promising cathode material for aqueous zinc ion batteries (AZIBs) because of its high reversible specific capacity, excellent rate performance and fast diffusion kinetics. However, its long-term cycle stability and compatibility with electrolytes have not met expectations. In this study, another metastable phase of vanadium dioxide—monoclinic VO2 (D)—is demonstrated to be a better choice as a cathode for AZIBs. Electrochemical results revealed that the as-prepared VO2 (D) hollow nanospheres delivered high reversible discharge capacity (up to 408 mA h g −1 at 0.1 A g −1 ), exceptional rate performance (200 mA h g −1 at 20 A g −1 ), and long cyclic endurance stability (cycling for 30 000 cycles with a low capacity fading rate of 0.0023% per cycle) in inexpensive 3 M ZnSO4 electrolyte. Furthermore, the electrochemical reaction mechanism was corroborated using ex situ XRD, HRTEM and XPS, showing that an interesting electrochemically induced phase transition from VO2 (D) to V2 O5 · x H2 O occured with the insertion/extraction of zinc ions. Finally, the prototype batteries assembled with our as-prepared VO2 (D) hollow nanospheres and the impressive performance of this electrode under high active material mass loading further reveal its high potential in practical applications.